2012
DOI: 10.1002/uog.12311
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting feasibility and quality of second‐trimester ultrasound scans in obese pregnant women

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 15 publications
(27 reference statements)
1
58
1
Order By: Relevance
“…This wider distribution of SFT measures in overweight and obese pregnant women was also observed by Fusch. 41 Our data demonstrated that SFT decreased significantly from the first measurement (SFT1) to the second (SFT2) in overweight and obese women (Table 1). Early research with small numbers of normal weight women using skin calipers and body composition demonstrated an increase in fat deposits from 6-10 to 28-35 weeks' gestation.…”
Section: Discussionmentioning
confidence: 50%
“…This wider distribution of SFT measures in overweight and obese pregnant women was also observed by Fusch. 41 Our data demonstrated that SFT decreased significantly from the first measurement (SFT1) to the second (SFT2) in overweight and obese women (Table 1). Early research with small numbers of normal weight women using skin calipers and body composition demonstrated an increase in fat deposits from 6-10 to 28-35 weeks' gestation.…”
Section: Discussionmentioning
confidence: 50%
“…Where it is a case of poor image quality due to the distorting effects of overlying tissue, it is less likely that a repeat transabdominal examination will improve the situation and a TV scan may be requested. Fuchs et al 3 suggested that moving the position of the foetus and using a more experienced sonographer may sometimes improve the result. However, if approaching the imaging from another plane or compressing the skin with the ultrasound transducer has no effect, then a repeat TA scan is not really indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of achieving a high-quality obstetric scan in women with a high BMI has always been an issue that is not getting any easier with the increasing rise in obesity within this population. [2][3][4] Uhden et al 5 found that the rate of obtaining inadequate images for assessing foetal heart defects, in patients where the foetus did have a defect, increased from 6.4% for a normal weight population to 17.4% in the obese population (BMI 30), and that these obese patients were significantly more likely to have a foetus with a heart defect (relative risk 2.04). Following the introduction of the NICE Guidelines in 2010, 2 our own department has introduced a midwife-led BMI clinic (BMI 30-34.9) and a consultant-led clinic (BMI >35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…– 31 As such, the AC measurement is faster and easier to obtain than the EFW in a term pregnancy, where the engaged head can make the HC and BPD measurements technically difficult and less reliable. It is also one of the measurements which appears to be more achievable in the obese population, with equivalence of image quality compared with patients of average BMI 41 . This may be an important factor in the gestational diabetic population, who are more likely to be obese and therefore more difficult to scan.…”
Section: Discussionmentioning
confidence: 99%